Breves danças à margem - A constituição de uma história artística da dança em Goiânia (1982-1986) - RIBEIRO, Luciana Gomes (2010)
This thesis investigated theoretical and methodological possibilities on the field of study of the Arts, in order to build a history of dance in the city of Goiânia. The body in dance was considered as the place in which this history happens, while different and interconnected concepts of the body, art and dance, and their historiographies, support this statement. Understanding the unique configuration of the dance phenomenon and its attention/tension as history, a more critical and conceptual approach was chosen using theories on the field of conceptual history, and history of oblivion, and from that point to invention, uncertainty and unpredictability. This pathway proved to be a key factor on the identification of the dance events being held in Goiânia between the years of 1982 and 1986. Therefore, to better understand these events, the dance history between 1973 and 1988 was investigated. This period of time was marked by the creation of the first institutions for the practice of dance in Goiânia and the outbreak of a new dance scene on the city. It was also a time of great invention and creation on this area in Goiânia, which prompted the city to an exclusive and active dialogue with the dance scenario in Brazil and internationally. The sources and documents studied pointed out interesting occurrences on the dance aesthetics of that time, highlighting its insertions and hierarchies. Some of the people and artwork of that time were prominent and produced other significant developments, very distinct from what was admitted by them, or even expected from them. Local postures and dance movements bearing traces of audacity and singularity were being created at that time, showing that a new kind of dance was emerging. The association made with this whole new dance scene is that of a production beyond Nietzsche, that does not necessarily is a dichotomy or an act of overcoming tradition, but an explosion. Dance on the void, created via its process-operation of existence. Artistic temporality, where history exists.